HPV Vaccine: Current Data, Efficacy, and Clinical Implications - Marut, Agnieszka; Kopeć, Karolina; Bartoszek, Aleksandra; Adamiuk, Julia; Biskup, Marta; Misiuk, Jagoda; Skuba, Adriana; Załuska, Katarzyna; Świdniak, Agnieszka; Nykiel, Sylwia (Quality in Sport, 2025)
Introduction and Purpose: Human papillomavirus (HPV) is a major cause of several cancers, including cervical cancer, and HPV vaccination is an effective method of preventing these diseases, especially before the initiation of sexual activity. The aim of this paper is to review current knowledge regarding HPV vaccines. It seeks to determine their effectiveness and their application in both primary and secondary prevention of HPV-related diseases. Materials and Methods: The review provides a summary of key information on the effectiveness, clinical aspects, and potential side effects following HPV vaccination. This analysis is based on peer-reviewed studies sourced from scientific databases such as PubMed. Results: Studies show promising results, with complete remission in most patients with genital warts and a skin cancer cases, such as squamous cell carcinoma (SCC), in patients receiving the Gardasil vaccine. Additionally, the vaccine shows potential effectiveness in treating epidermodysplasia verruciformis (EV), particularly in immunocompromised patients, where clinical improvement and HPV DNA clearance have been observed. Data from countries such as Thailand, Tanzania, and India suggest that a single dose of the HPV vaccine may offer protection comparable to multiple doses, making vaccination more cost-effective and accessible in resource-limited countries, supporting public health goals to reduce cervical cancer cases. Furthermore, the introduction of new treatment methods and ongoing research into HPV vaccines, including DNA vaccines and PD-L1 blockade, may provide additional therapeutic options in the future. Conclusion: Vaccinations show a herd effect, reducing the number of cases of genital warts and respiratory papillomatosis, and their widespread implementation in health programs can significantly impact the reduction of HPV-related cancers worldwide.